Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Microbially induced hydroxyapatite improves simultaneous nitrogen and phosphorus removal in aerobic granular sludge - Fan Yang; Gonglei Wang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Jinsong Guo; Fang Fang (Bioresource Technology, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Low-valent cation substitution in high-entropy layered oxides inhibits Jahn–Teller distortion and accelerates sodium storage kinetics - Mengting Du; Rui Wang; Fan Wang; Lijing Yan; Quan Zong; Guoying Wei; Feifan Chang; Lu Jin; Qiaoling Kang (Chemical Engineering Journal, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Microbial niches and metabolism drive spatial heterogeneity of hydroxyapatite precipitation in aerobic granular sludge - Gonglei Wang; Fan Yang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Fang Fang; Jinsong Guo (Water Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Centrifuge modeling of static liquefaction in completely decomposed granite fill slopes - Zhun Liu; Yu Zhao; Teng Liang; Fan He; Rui Zhang; Zhuang Yan; Daosheng Ling; Liangtong Zhan; Yunmin Chen (Engineering Geology, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Joint Arctic Sea Ice Forecasting Based on Graph-Structured Spatial Modeling and Temporal Transformers - Bowen Liu; Caiping Xi; Yukai Ma; Rui Zhai; Ting Ma; Fan Yan (Journal of Marine Science and Engineering, 2026)
Rapid changes in Arctic sea ice exert significant impacts on regional climate feedbacks and high-latitude maritime activities, increasing the demand for accurate short-term forecasting of key sea ice variables. This study proposes a GraphTransformer-based framework for joint forecasting of sea ice thickness (SIT) and sea ice concentration (SIC), designed to address their strong spatiotemporal coupling under irregular Arctic Ocean geometries. A static spatial graph is constructed over effective Arctic marine grid cells, where neighborhood aggregation is applied at each time step to explicitly encode spatial correlations. A shared-parameter temporal Transformer is subsequently employed to model node-level long-range temporal dependencies and to perform direct multi-step forecasting. The model generates 14-day daily forecasts of SIT and SIC in a single forward pass. Experiments are conducted using multi-source daily data spanning from 1 January 2019 to 15 May 2025, with evaluation restricted to valid marine grid nodes. Results indicate that the proposed GraphTransformer achieves either the best or second-best performance among the compared models in multi-step forecasting accuracy. Ablation experiments further confirm the critical role of graph-based spatial encoding in enhancing spatial coherence and mitigating error propagation.

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Human milk oligosaccharides improve intestinal barrier integrity and immune homeostasis through the microbial metabolite butyrate - Peng Zhang; Chonghua Fan; Jiayue Li; Yalu Yan; Yumeng Zhang; Rui Zhang; Bailiang Li; Sufang Duan (Food Bioscience, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

Associations of outdoor artificial light at night exposure with telomere length and mitochondrial DNA copy number in children and adolescents: Examining sex-specific associations - Gaojie Fan; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; Liqin Hu; Xiaoning Lei; Youjie Wang; Mingyang Wu; et al. (Environmental Research, 2026)

Ferroptosis-mediated ocular developmental toxicity of biodegradable nanoplastics in zebrafish - Yutong Liu; Lifan Fan; Nanxin Ma; Rui Wang; Qiqi Yan; Chen Chen; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2026)